2022
DOI: 10.1038/s41598-022-19493-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal evolution characteristics of land use and habitat quality in Shandong Province, China

Abstract: To explore the sustainable mechanism of land use and habitat quality, the present study examined the land cover data of Shandong Province from 1980 to 2020 to understand the spatial–temporal evolution characteristics of land use. The “Integrated Valuation of Environmental Services and Trade-off” (InVEST-HQ) model and spatial auto-correlation model were further employed to evaluate the habitat quality and analyze the relationship between its spatial distribution pattern and land use type. Our results suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The spatial differentiation of eco-environmental quality was consistent with the results of previous studies [8,48], and the spatial distribution of ecological and environmental quality largely coincides with the distribution of land use. The conversion of forest and cropland to construction land and the mutual conversion between forest and cropland are the reasons for the deterioration of the eco-environment quality of CZTCA.…”
Section: Evolution Of Eco-environmental Effects In the Past 20 Yearssupporting
confidence: 89%
“…The spatial differentiation of eco-environmental quality was consistent with the results of previous studies [8,48], and the spatial distribution of ecological and environmental quality largely coincides with the distribution of land use. The conversion of forest and cropland to construction land and the mutual conversion between forest and cropland are the reasons for the deterioration of the eco-environment quality of CZTCA.…”
Section: Evolution Of Eco-environmental Effects In the Past 20 Yearssupporting
confidence: 89%
“…For example, the expansion of urban construction has severely damaged natural habitat, leading to biodiversity loss 26,27 . In addition, natural factors (altitude, slope, climate) and land use type also significantly influence changes in HQ 28,29 . Therefore, determining the factors that influence HQ can provide a basic information for biodiversity maintenance, improvement of the ecological environment, and enhancement of ecosystem service functions 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The study of landscape patterns can provide an accurate and significant evaluation of ecosystems to recognize the areas with high HQ and degraded lands. In order to improve our understanding of the ecological condition in a region and make better decisions for land management, it has been confirmed that combining HQ with landscape metrics is an adequate indicator for assessing ecosystems 20 , as well as Zheng and Li 54 reported that effective LU/LC planning based on habitat quality is essential for achieving sustainable regional development. About natural ecosystems such as rangelands and forests, decision-makers should recover the natural biodiversity system 55 .…”
Section: Discussionmentioning
confidence: 97%
“…Especially the LU/LC classification error can introduce skepticism in the HQ results, particularly in the future. Final, a method for validating the HQ score is not mentioned in the model manual or references 10 , 14 , 54 .…”
Section: Discussionmentioning
confidence: 99%